Bone regeneration in periodontal therapy: exploring the compressive strength and structural characteristics of calcium sulfate-chitosan composites - Mohamad, Ikhwan Hakimi; Nik Mahmood, Nik Zarina; Ariffin, Farha (Faculty of Dentistry, Universiti Teknologi MARA, 2025)
This study aims to investigate the mechanical properties and structural characteristics of innovative calcium sulfate-chitosan (CS-CHT) biomaterials on human periodontal ligament fibroblasts (PDLF) to advance periodontal regeneration. The biomaterials were prepared by mixing calcium sulfate with distilled water and chitosan, followed by molding into cylindrical samples. Human periodontal ligament fibroblasts (PDLF) were grown in a complete medium until they reached 90% confluency, then seeded onto the CS-CHT biomaterial. The compressive strength of the samples was tested using a universal testing machine, with measurements taken at 24 hours, 48 hours, 72 hours, and one week. Scanning electron microscope (SEM) imaging was used to analyze the structural characteristics. The results showed that the compressive strength of CS-CHT biomaterials increased over time, surpassing that of CS alone after one week, with average compressive strengths ranging from 2.93 MPa to 5.61 MPa. SEM images revealed a crystalline arrangement and textured surface with pores ranging from 6.0 µm to 89.5 µm. Successful adhesion of PDLF to the biomaterials was observed, with cytoplasmic extensions visible in the SEM images. There were no significant differences between the two groups at various time points based on the independent t-test.